# What is the simplified form of (x - 2)(2x + 3)?

**Solution:**

The simplified form can be obtained by finding the product of the given polynomials.

We can simplify (x - 2)(2x + 3) as:

(x - 2)(2x + 3) = x(2x + 3) - 2(2x + 3)

= 2x^{2} + 3x - 4x - 6

= 2x^{2} - x - 6

Thus, the simplified form of (x - 2)(2x + 3) = 2x^{2} - x - 6, which is a quadratic expression.

## What is the simplified form of (x - 2)(2x + 3)?

**Summary:**

The simplified form of (x - 2)(2x + 3) = 2x^{2} - x - 6.

Math worksheets and

visual curriculum

visual curriculum